Epistemological Probabilism and the Ethics of Equilibrium: Rethinking Environmental Policy in a Complex World - Ekanem, Samuel Aloysius; Egbai, Mary Julius; Egbai, Julius Michael (Studia Ecologiae et Bioethicae, 2025)
The relationship between human epistemology and environmental ethics has long influenced formulation of policies aimed at mitigating ecological crises. Among these, epistemological probabilism, an approach that acknowledges the uncertainty and variability inherent in predicting environmental outcomes, has profoundly shaped debates on environmental policy. This paper argues that probabilistic interpretations of ecological data, often characterized by opposing claims and speculative forecasts, contribute to policy indecision and hinder the adoption of coherent and effective environmental strategies. These divergences can result in either overly cautious or insufficiently responsive measures, both of which have adverse effects on global ecological health. To address these challenges, the paper proposes an ethics of equilibrium, a dynamic and context-sensitive ethical framework designed to navigate the uncertainties inherent in environmental decision-making. By emphasizing balance, adaptability, and context-specificity, this framework advocates for policies that align with the immediate and long-term ecological realities of particular societies while fostering global sustainability. The ethics of equilibrium rejects one-size-fits-all solutions and instead encourages a pragmatic yet ethically grounded approach to environmental governance. Through a critical examination of probabilistic reasoning in environmental epistemology, this paper highlights the need for an integrated ethical and policy model that transcends binary or static paradigms. By embedding flexibility and equilibrium within environmental policies, societies can better address the complexity and unpredictability of ecological challenges while remaining committed to ethical stewardship of the planet.